Towards detailed combustion characteristics and linear stability analysis of premixed ammonia‒hydrogen‒air mixtures - Jun Cheng; Bo Zhang (Applications in Energy and Combustion Science)
In this study, premixed ammonia‒hydrogen‒air mixtures at different pressures (50∼300 kPa), equivalence ratios (0.7∼1.5), and hydrogen concentrations (9∼50.00 %) were centrally ignited in a closed vessel, and the propagation of a spherical flame was recorded via a high-speed schlieren system. To accurately measure the laminar burning velocity, an AI model (RTMDet model) was trained on the schlieren images obtained in the experiments to mark the flame profile and calculate the flame area. The corresponding laminar combustion parameters were measured. Additionally, linear stability theory was applied to evaluate the critical conditions for the onset of flame instability. The results indicate that the hydrodynamic instability exhibits greater sensitivity to the initial pressure and equivalent ratio, whereas the molecular diffusion is remarkably sensitive to the hydrogen concentration in lean conditions. For the lean mixture, flame destabilization is enhanced by the thermal‒diffusion instability and curvature effect, whereas for the rich mixture, both the hydrodynamic instability and thermal‒diffusion instability is diminished, and flame stabilization is determined by the stretching effect. The critical Peclet number monotonically decreases as the equivalence ratio decreases and the hydrogen concentration increases. Hydrodynamic instability consistently promotes flame destabilization, whereas thermal-diffusion instability does not invariably contribute positively; for the lean mixtures, both the strain rate and curvature make the flame unstable, whereas they make the flame stable for the rich mixtures. The hydrogen concentration has a relatively limited effect on the strain rate and curvature. Additionally, the critical Karlovitz number indicates that flames in rich conditions are less susceptible to disturbances and instability. This study enhances the understanding of intrinsic instability mechanisms during flame propagation in ammonia‒hydrogen blended fuels, improves insights into their combustion characteristics, and provides a reference for optimizing combustion performance.